2015
DOI: 10.1007/s11307-015-0898-5
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using an Enzymatically Activatable Fluorescence Probe for the Rapid Evaluation of Pancreatic Tissue Obtained Using Endoscopic Ultrasound-Guided Fine Needle Aspiration: a Pilot Study

Abstract: Purpose: Endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) is the most reliable method for the histological diagnosis of pancreatic tumors. Rapid on-site fluorescence-guided histological diagnosis was evaluated by topically applying an enzymatically activatable probe onto the EUS-FNA samples; the probe fluoresces in the presence of γ-glutamyltranspeptidase.Procedures: EUS-FNA was performed in 10 pancreatic tumors. After topical application of the probe, signal intensity was measured using a fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Encouraged by these results, the authors lately demonstrated that 3 was also efficient for intraoperative detection of breast, oral, head, and neck cancers by topically spraying the probe . Moreover, the successful application of 3 onto endoscopic ultrasound‐guided fine‐needle aspiration samples for the rapid evaluation of pancreatic tissues was further investigated; this confirmed the high capacity of 3 for cancer detection …”
Section: Activatable Fluorescence Probes For Ggtmentioning
confidence: 70%
See 2 more Smart Citations
“…Encouraged by these results, the authors lately demonstrated that 3 was also efficient for intraoperative detection of breast, oral, head, and neck cancers by topically spraying the probe . Moreover, the successful application of 3 onto endoscopic ultrasound‐guided fine‐needle aspiration samples for the rapid evaluation of pancreatic tissues was further investigated; this confirmed the high capacity of 3 for cancer detection …”
Section: Activatable Fluorescence Probes For Ggtmentioning
confidence: 70%
“…Considering that two-photon fluorescence imaging, in which af luorophorea bsorbst wo low-energy NIR photons upon excitation with aN IR pulse laser and emits shorter wavelength, highere nergy fluorescence, hast he advantages of deep-tissue penetration, low tissue autofluorescence, and high spatial resolution for living cells and tissues, [31] aG GT-activatable twophoton fluorescencei maging probe (15)h as also been reported by Wu and co-workers. [32] In this system,adicyanomethylene-4H-pyran (DCM)d erivative with al arge two-photon absorption( TPA) cross-section, strong ICT ability,a nd good fluorescence quantum yield wase mployed as the TPAf luorophore.…”
Section: Activatable Fluorescencep Robes For Ggtmentioning
confidence: 99%
See 1 more Smart Citation
“…gGlu-HMRG is nonfluorescent in its native state but is rapidly hydrolyzed by GGT to generate HMRG, which emits fluorescence with a peak wavelength of ~520 nm 12 . So far, we have demonstrated efficacy of cancer imaging with topical administration of gGlu-HMRG using various human cancer tissues such as breast cancer 13, 14 , head and neck cancer 15 , lung cancer 16 , primary colorectal cancer 17 , pancreatic cancer 18 and oral cancer 19 . Because overexpression of GGT has been observed in HCC and intrahepatic cholangiocarcinoma (ICC) 6, 2022 , we hypothesized that gGlu-HMRG could also be used for identification of hepatic malignancies during liver resection.…”
Section: Introductionmentioning
confidence: 99%
“…These probes can be sprayed onto tissue surfaces that are suspected of harboring tumors and require a lower dose than systemic administration (32,34). Human clinical studies of these probes revealed that on-site topical administration of aspirated specimens provided rapid visualization and diagnosis of pancreatic tumors (35). Work with "always on" fluorescent molecules has demonstrated that probes can also be topically applied directly to esophageal neoplasia in patients (34).…”
Section: Introductionmentioning
confidence: 99%